Steps towards numerical verification of the terahertz in‐line measurement of tablet mixing by means of discrete element modelling. Issue 11 (13th August 2018) - Lin, Hungyen; Pei, Chunlei; Markl, Daniel; Shen, Yaochun; Elliott, James A.; Zeitler, J. Axel
Abstract : In recent years, terahertz in‐line sensing has been used to monitor the film coating thickness of individual pharmaceutical tablets during the coating process. In the previous work, the in‐line measurements were verified against off‐line measurements of samples from the same population. Here, we report on our recent progress to further verify the validity of the terahertz in‐line measurement modality using discrete element modelling for an artificial lab‐scale tablet mixing process inside a tablet pan coater. By coupling discrete modelling with a ray‐tracing method, it is then possible to estimate the cumulative measurements taken, which in turn can guide towards the fine‐tuning of the selection criteria as part of measurement analysis.